High resolution vs conventional esophageal manometry in the assessment of esophageal motor disorders in patients with non‐cardiac chest pain. Issue 6 (29th December 2017) - Akinsiku, O.; Yamasaki, T.; Brunner, S.; Ganocy, S.; Fass, R.
Abstract: Background: High‐resolution esophageal manometry (HREM) has become a leading tool in the assessment of esophageal motor disorders, replacing conventional manometry. However, there is limited data about the contribution of HREM as compared with conventional manometry to the assessment of esophageal motor disorders in patients with non‐cardiac chest pain (NCCP). The aim of the study was to compare the distribution of esophageal motor disorders in patients with NCCP using HREM as compared with conventional manometry and to determine if HREM improved diagnosis of these disorders. Methods: In this study, we included 300 consecutive patients with NCCP who underwent either HREM or conventional manometry over a period of 10 years. A total of 150 patients had conventional manometry and the other 150 patients HREM. The Chicago 3.0 classification and the Castell and Spechler classification were used to determine the esophageal motor disorder of NCCP patients undergoing HREM and conventional manometry, respectively. Key Results: In both HREM and the conventional manometry groups, normal esophageal motility was the most frequent finding (47% and 36%; respectively, P  = .054). Hypotensive lower esophageal sphincter was the most common motility disorder identified by conventional manometry (27.3%), while ineffective esophageal motility was the most common esophageal motor disorder identified by HREM (25.3%). Conclusions & Inferences: There is a discrepancy in the type of esophageal motor disorders identified by HREM as compared with conventional manometry in NCCP patients. Hypotensive motility disorders are the most commonly diagnosed by both manometric techniques.